Metode ACQ Sebagai Pendekatan Kreatif Untuk Meningkatkan Kemampuan Menghafal Anak Usia Dini (Prosiding Keislaman dan Sains, 2025)
This study aims to analyze the effectiveness of the ACQ (Aku Cinta Al-Qur'an) method as a creative approach in improving the memorization ability and creativity of early childhood. This method uses a multisensory approach involving visual, auditory, and kinesthetic elements to create an interactive and enjoyable learning experience. A qualitative descriptive approach was used in this study, with data collected through observation, interviews, and documentation from formal and informal educational institutions. The results showed that the ACQ method was effective in improving children's memorization ability, extending concentration duration, and fostering interest in learning. In addition, this method also stimulates children's creativity through activities such as movements related to the meaning of verses, visualization, and games. The main challenges in implementing this method involve the readiness of educators and a supportive learning environment. This study concludes that the ACQ method makes a significant contribution to holistic religion-based education, especially for early childhood.
Keywords: ACQ Method; Creativity; Early Childhood; Memorizing the Qur'an